Development of Dembo-PCR for cattle in accordance with Japanese livestock quarantine guidelines - OBA, Mami; IMAI, Ryo; TESHIMA, Natsuko; NODA, Miho; NUNOMURA, Yuka; KAKINUMA, Seiichi; ITO, Kazuki; OGURO, Masashi; KONAKA, Kazunari; ENOMOTO, Tomoya; MORITA, Hisamoto; OMATSU, Tsutomu; et al. (Journal of Veterinary Medical Science, 2025)
Detection of microorganisms from bovine using real-time PCR (Dembo-PCR) is a comprehensive detection technique that was developed to detect pathogens causing bovine diseases. In Japan, the definitive tests for monitored infectious diseases, which are defined by law, are carried out at government agencies. On the other hand, the existence of pathogens other than monitored infectious diseases are not well understood. From the perspective of livestock quarantine, it is important to make it possible to identify pathogens other than monitored infectious diseases, so we extended the existing Dembo-PCR system in this study. In particular, the number of targets other than monitored infectious disease was increased. The new version of Dembo-PCR may be useful in elucidating new pathologies associated with multiple pathogens.